A Cylindrically Symmetric and Static Anisotropic Fluid Spacetime and the Naked Singularity. (8th April 2018) - Ahmed, Faizuddin; Rahaman, Farook
Abstract : A cylindrically symmetric and static solution of Einstein's field equations was presented. The spacetime is conformally flat and regular everywhere except on the symmetry axis where it possesses a naked curvature singularity. The matter-energy source anisotropic fluids violate the weak energy condition (WEC) and diverge on the symmetry axis. We discuss geodesics motion of free test-particles near to the singularity, geodesic expansion in the metric to understand the nature of singularity which is naked or covered, and finally the C-energy of the spacetime.